2013
DOI: 10.1177/0734282913511431
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Characteristics of the Korean Mental Health Continuum–Short Form in an Adolescent Sample

Abstract: There have been few research studies to examine the positive mental health of Asian adolescents. The aim here is to examine the factorial structure, internal consistency, test-retest reliability, and convergent/discriminant validity of a Korean version of the Mental Health Continuum–short form (K-MHC-SF), a newly developed self-report scale for positive mental health assessment, in a sample of South Korean adolescents. The Korean sample comprised 547 high school students (57% were female), ranging in age from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
53
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(70 citation statements)
references
References 22 publications
14
53
1
2
Order By: Relevance
“…Studies in the general population have shown that the MHC‐SF is a reliable and valid instrument to comprehensively measure emotional, psychological, and social well‐being (De Carvalho et al., ; Hides et al., ; Joshanloo, ; Joshanloo et al., ; Karaś et al., ; Keyes et al., ; Lamers et al., ; Lim, ; Perugini et al., ; Petrillo et al., ; Robitscheck & Keyes, ; Salama‐Younes, & Ismaïl, ). Furthermore, studies in the general population have provided evidence for the dual continua model of well‐being and psychopathology (Gilmour, ; Keyes, ; ; ; Keyes et al., ; Keyes et al., ; Lamers et al., ; Lamers, Westerhof, Bohlmeijer, & Keyes, ; Perugini et al., ; Petrillo et al., ; Renshaw & Cohen, ; Westerhof & Keyes, , ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies in the general population have shown that the MHC‐SF is a reliable and valid instrument to comprehensively measure emotional, psychological, and social well‐being (De Carvalho et al., ; Hides et al., ; Joshanloo, ; Joshanloo et al., ; Karaś et al., ; Keyes et al., ; Lamers et al., ; Lim, ; Perugini et al., ; Petrillo et al., ; Robitscheck & Keyes, ; Salama‐Younes, & Ismaïl, ). Furthermore, studies in the general population have provided evidence for the dual continua model of well‐being and psychopathology (Gilmour, ; Keyes, ; ; ; Keyes et al., ; Keyes et al., ; Lamers et al., ; Lamers, Westerhof, Bohlmeijer, & Keyes, ; Perugini et al., ; Petrillo et al., ; Renshaw & Cohen, ; Westerhof & Keyes, , ).…”
Section: Discussionmentioning
confidence: 99%
“…They answered questions like “During the past month, how often did you feel: happy (emotional well‐being); confident to think or express your own ideas and opinions (psychological well‐being); that you had something important to contribute to society (social well‐being). The MHC‐SF has good psychometric qualities in the general population (De Carvalho et al., ; Hides et al., ; Joshanloo, ; Joshanloo, Wissing, Khumalo, & Lamers, ; Karaś et al., ; Keyes et al., ; Lamers et al., ; Lim, ; Perugini et al., ; Petrillo et al., ; Salama‐Younes & Ismaïl, ). The psychometric properties of the MHC‐SF in the psychiatric population will be examined in the present study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Flourishing mental health is the highest level of emotional, psychological, and social well-being. The Mental Health Continuum Short Form (MHC-SF) appears to have cross-cultural utility (Joshanloo et al 2013; Keyes et al 2008; Lim 2013). …”
Section: Positive Mental Health Continuummentioning
confidence: 99%
“…The MHC-SF consists of 14 items assessing emotional well-being (three items), social well-being (five items), and psychological well-being (six items) on a six-point scale and is an abbreviated version of the original longer instrument ("Mental Health Continuum-Long Form," Keyes, 2008, available from http://booksite.elsevier.com/9780123745170). The non-orthogonal three-factor structure underlying both the long form and the short form of this instrument has been validated repeatedly (e.g., Gallagher, Lopez, & Preacher, 2009;Jaotombo, 2014;Joshanloo, Rostami, & Nosratabadi, 2006;Joshanloo, Wissing, Khumalo, & Lamers, 2013;Karaś, Cieciuch, & Keyes, 2014;Keyes, 2005Keyes, , 2009bKeyes et al, 2008;Lamers, Westerhof, Bohlmeijer, ten Klooster, & Keyes, 2011;Lim, 2014;Petrillo, Capone, Caso, & Keyes, 2015;Robitschek & Keyes, 2009;Salama-Younes, 2011a,b;Salama-Younes & Ismaïl, 2011). Emotional well-being reflects the traditional philosophical concept of hedonia; psychological well-being and social well-being reflect two different aspects of the traditional philosophical concept of eudaimonia.…”
mentioning
confidence: 99%